The impact of implementing islamic business communication ethics and product innovation on consumer satisfaction - Ahmad Misbah; Abdul Muhyi; Mukhamad Ainul Yaqin (Institute of Accounting Research and Novation (IARN), 2025)
Previous studies on Al-Ghazali have predominantly focused on his philosophical and theological thought within the context of classical Islam, without specifically examining how these ideas were received and applied by scholars in the Malay-Indonesian world. This study addresses that gap by exploring the creative reception of Al-Ghazali’s thought in the 19th-century Kāsifatussajā, a fiqh work by Syeikh Nawawi al-Bantani. The aim is to identify and analyze the manifestation of Al-Ghazali’s philosophical-theological ideas within Nawawi’s fiqh-ethical-transformative approach. Employing a qualitative descriptive method through library research and framed within Jaussian reception theory, this study finds that Nawawi integrated reason and revelation, emphasized the spiritual dimension of Islamic law, and adopted a moderate approach in issuing legal opinions. The findings reveal that Nawawi did not merely reproduce Al-Ghazali’s ideas but reconstructed them to address the challenges of colonialism, identity crisis, and the need for a spiritually grounded legal ethics in the Nusantara. This research contributes to a deeper understanding of the dynamic transmission of classical Islamic intellectual heritage and its relevance in local socio-cultural contexts.